ECOLOGICAL EDUCATION IN PRIMARY CLASSES FORMATION OF PEDAGOGICAL CONDITIONS OF DEVELOPMENT - Uljamol SHERMATOVA (Scholar Express Journal, 2024)
In this article, the creation of pedagogical conditions in primary classes, the development of ecological education, instilling love for nature, educating students in the spirit of love for the motherland, as well as reflections of students on environmental protection and nature conservation during the lesson reported.
Keywords: ecology; education; pedagogy; technologies